2021
DOI: 10.1007/s10961-021-09885-y
|View full text |Cite
|
Sign up to set email alerts
|

How do human capital and R&D structure facilitate FDI knowledge spillovers to local firm innovation? a panel threshold approach

Abstract: This paper examines how local firms’ structure of human capital and R&D strategies influence their absorption of FDI knowledge spillovers. Using a unique dataset of Chinese firms in Beijing Zhongguancun Science Park from 2009 to 2015, our panel endogenous threshold models confirm two thresholds for human capital diversity and one threshold for R&D diversity in facilitating FDI spillovers. When human capital diversity is below its second threshold, FDI presence positively influences local firms’ innovat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 79 publications
3
22
0
Order By: Relevance
“…Recent studies on economic growth assume that formal skills embodied in the labor force (human capital) could have an important impact on the growth process if they give rise to more intensive R&D and a faster rate of technological progress (Bassanini and Scarpetta, 2001; Guo et al. , 2021; Blanco et al.…”
Section: Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on economic growth assume that formal skills embodied in the labor force (human capital) could have an important impact on the growth process if they give rise to more intensive R&D and a faster rate of technological progress (Bassanini and Scarpetta, 2001; Guo et al. , 2021; Blanco et al.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Recent studies on economic growth assume that formal skills embodied in the labor force (human capital) could have an important impact on the growth process if they give rise to more intensive R&D and a faster rate of technological progress (Bassanini and Scarpetta, 2001;Guo et al, 2021;Blanco et al, 2016). For instance, in the United States, Blanco et al (2016) document a positive effect of R&D spending on state GDP and that increasing human capital is linked to higher R&D elasticity.…”
Section: Jrf 235mentioning
confidence: 99%
“…Regarded as the important resources to significantly influence the firms' operation processes, researchers have began incorporating the management of human capital and its impact on innovation (Afcha and Lucena, 2022;Salimi and Della Torre, 2022). However, the previous studies on firm innovation mainly discussed the importance of the stock of human capital, and less discussed how the structure of human capital affects firm innovation (Guo et al, 2022). Generally, human capital structure refers the difference level (Jabbour et al, 2017).…”
Section: Talent Policy and Human Capital Structurementioning
confidence: 99%
“…Literature on IP can be generally divided into enterprise IP, industrial IP, regional IP, and other perspectives, and the measurement criteria can be generally divided into two categories: Measurement of macro data and collection of questionnaires. When measuring enterprise IP, Revenue from new product sales [13], per capita sales revenue of new products [14,15], and a number of patent applications [16][17][18] are often used. Of course, the sales revenue of new products and the number of authorized invention patents are also used for comprehensive measurement [19].…”
Section: The Measurement Of Ipmentioning
confidence: 99%
“…In the past three years, the research literature has focused on the relationship between FDI and industrial innovation. It is believed that FDI significantly promotes industrial IP [7], and enterprise IP [13]. Literature studies on foreign R&D activities in Belgium found that spillover of foreign R&D usually occurs more frequently than FDI [10].…”
Section: Randd and Innovationmentioning
confidence: 99%